EXPLORING EFL STUDENTS’ PERCEPTIONS OF SCHEMA-ACTIVATED MULTIMEDIA INSTRUCTION FOR DEVELOPING CRITICAL LISTENING SKILLS - Dwi Rara Saraswaty; Hadiyanto; Eddy Haryanto (Indonesian EFL Journal, 2026)
Critical listening is an advanced listening skill that requires learners to interpret, evaluate, and synthesize spoken information in academic discourse. However, listening instruction in many EFL contexts still relies heavily on audio-only materials, which may limit learners’ engagement in higher-order listening processes. This study explores EFL students’ perceptions of schema-activated multimedia instruction for developing critical listening skills. The study adopted an explanatory perception-focused mixed-methods design. The participants were 30 students from the experimental group of a larger instructional study in an Indonesian university. Quantitative data were collected through a 20-item closed-ended questionnaire, while qualitative data were obtained from six open-ended questionnaire items to provide explanatory insights into students’ learning experiences. Descriptive statistics were used to analyze the quantitative data, and thematic analysis was employed to interpret the qualitative responses. The results indicate that students demonstrated highly positive perceptions of schema-activated multimedia instruction across all instructional dimensions. Multimedia usage received the highest perception scores, followed by prior knowledge activation and critical listening support. Qualitative findings further revealed that schema activation enhanced cognitive readiness, multimedia support provided structural clarity and reduced cognitive load, and the instructional design encouraged metacognitive monitoring, confidence, and engagement during listening tasks. Overall, students perceived schema-activated multimedia instruction as more supportive and manageable than traditional audio-only listening activities. These findings highlight the importance of integrating schema activation and multimedia scaffolding in EFL listening instruction to facilitate learners’ engagement in higher-order listening processes, particularly critical listening in academic contexts.